ATRA-induced NEAT1 upregulation promotes autophagy during APL cell granulocytic differentiation. - Doudou Tang; Huihui Wang; Yafeng Jiang; Mingjie Chen; Guangsen Zhang; Shangjie Wu; Yewei Wang (PLoS ONE)
Aims Acute promyelocytic leukemia (APL) progresses quickly and often leads to early hemorrhagic death. Treatment with all-trans retinoic acid (ATRA) promotes differentiation of APL cells and clinical remission, making APL a potentially curable malignancy. Understanding how ATRA works may lead to new treatments for other types of leukemia. Long non-coding RNA NEAT1 has been implicated in the differentiation of APL cells. This study aims to elucidate the specific role of NEAT1 in the granulocytic differentiation of APL. Methods The influence of NEAT1 on autophagy and PML/RARα degradation was assessed using western blot assays. The impact of NEAT1 on the expression of autophagy-related genes was evaluated through quantitative real-time RT-PCR. Mechanistic insights into the role of NEAT1 in modulating autophagy were supported by RNA immunoprecipitation and RNA pulldown assays. Key findings Knockdown of NEAT1 suppressed autophagy and attenuated ATRA-induced PML/RARα degradation and granulocytic differentiation of APL cells. Subsequent screening of autophagy-related genes demonstrated that silencing NEAT1 impaired the ATRA-induced upregulation of ATG10 and ATG12. Mechanistic investigations revealed that the RNA-binding protein TAF15 interacted with NEAT1, synergistically stabilizing the mRNA of ATG10 and ATG12. Furthermore, knockdown of NEAT1 impaired the interactions between TAF15 and the mRNAs of ATG10 and ATG12, thereby compromising their mRNA stability. Significance Our study elucidates the critical role of NEAT1-mediated autophagy in the differentiation of APL cells and delineates the molecular mechanism by which upregulation of NEAT1 enhances autophagy. Specifically, NEAT1 binds to the RNA-binding protein TAF15, which in turn stabilizes the mRNA of both ATG10 and ATG12.